EFISIENSI ESKALASI JARINGAN IRIGASI MELALUI PROGRAM PERCEPATAN PENINGKATAN TATA GUNA AIR IRIGASI (P3-TGAI) DI KOTA SOLOK - Fernando, Rangga; Araska, Wahyu; Rianda, Hasbi (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2025)
The city of Solok, which is located in West Sumatra, with a population of 81,059 people, has limited agricultural land of 875.6 hectares and produces 5,430 tons of rice, which has experienced a decline in rice production since 2019. This decline in rice production was caused by irrigation constraints, which prompted the government to implement the Acceleration Program for Irrigation Water Use Improvement/P3TGAI to improve the irrigation network which involves community participation, in this case the Water User Farmers Association (P3A). This research compares the efficiency of cost planning and budgeting for irrigation improvements in the Bdr Lembang irrigation area using the Unit Price Analysis (AHSP) approach. Data collected includes primary and secondary surveys, with a focus on existing irrigation conditions. The results showed that there are 5 determinants of the success of the self-management project for P3-TGAI, such as good communication between parties involved in the project (95.95); appropriate/appropriate work planning (91.89); monitoring of the project by the parties involved (89.19); ability to solve project problems by the parties involved (83.78); proper cost management by the parties involved (83.78). Then, there are 10 aspects that determine the success of P3-TGAI self-management projects, these factors are formed from the highest index in each aspect surveyed. analysis show the difference between the implementation of self-management and contracting in the use of materials and personnel because the volume of the channel length in self-managed work is 368 meters, whereas if it is contractual the channel length volume is 345.32 meters. Thus highlighting the need for effective resource management in irrigation projects.